Hotaru no haka = Grave of the fireflies [videorecording (Blu-ray + DVD)] - Mamiya, Michio, 1929-2024 (GKids, 2025)
"When an American air raid kills their mother in the final days of World War II, 14-year-old Seita and his 4-year-old sister Setsuko are left to fend for themselves in the devastated Japanese countryside. After falling out with their only living relative, Seita does his best to provide for himself and his sister by stealing food and making a home in an abandoned bomb shelter. But with food running short, the siblings can only cling to fleeting moments of happiness in their harsh reality."